Nature and Space in Contemporary Scottish Writing and Art - Manfredi, Camille. author. aut Link
XII, 217 p. 16 illus.
Keywords: This book examines how contemporary Scottish writers and artists revisit and reclaim nature in the political and aesthetic context of devolved Scotland. Camille Manfredi investigates the interaction of landscape aesthetics and strategies of spatial representation in Scotland’s twenty-first-century literature and arts, focusing on the apparatuses designed by nature writers, poets, performers, walking artists and visual artists to physically and intellectually engage with the land and re-present it to themselves and to the world. Through a comprehensive analysis of a variety of site-specific artistic practices, artworks and publications, this book investigates the works of Scotland-based artists including Linda Cracknell, Kathleen Jamie, Thomas A. Clark, Gerry Loose, John Burnside, Alec Finlay, Hamish Fulton, Hanna Tuulikki and Roseanne Watt, with a view to exploring the ongoing re-invention of a territory-bound identity that dwells on an inclusive sense of place, as well as on a complexrenegotiation with the time and space of Scotland.